2008
DOI: 10.1007/s10800-008-9681-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electrochemical properties of nickel hydroxide electrodes with cobalt additives

Abstract: In this article,cobalt additives are introduced into nickel hydroxide electrodes by two incorporation methods-co-precipitated cobalt hydroxide during the nickel hydroxide synthesis or post-added CoO with nickel hydroxide. The results of X-ray diffraction, cyclic voltammetry, electrochemical impedance spectroscopy, and charge-discharge tests indicate that (i) the diffraction peaks show a decrease in intensity and increase in the half peak breadths for Ni(OH) 2 with co-precipitated cobalt hydroxide; (ii) the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Glasses' properties for instance are hard to predict because there is not a current theoretical framework that accurately models glasses [58]. Another example, is how new methods of electrode synthesis are developed [61][62][63], where a two stage lithiation process was developed and it can be Co free. Expanding on Figure 6, various software applications are available to simulate different components of a battery.…”
Section: Solid State Electrolyte Materialsmentioning
confidence: 99%
“…Glasses' properties for instance are hard to predict because there is not a current theoretical framework that accurately models glasses [58]. Another example, is how new methods of electrode synthesis are developed [61][62][63], where a two stage lithiation process was developed and it can be Co free. Expanding on Figure 6, various software applications are available to simulate different components of a battery.…”
Section: Solid State Electrolyte Materialsmentioning
confidence: 99%
“…Other hydroxide, Co(OH) 2 , has been widely used as an additive to Ni(OH) 2 in order to improve alkaline secondary batteries [17,18,19], these improvements being attributed to an increase of both ionic and electronic conductivities. Jafarian et al [20] have reported a good oxidation of methanol at glassy carbon electrodes modified with cobalt hydroxide.…”
Section: -Introductionmentioning
confidence: 99%